Door locking system using Android mobile device based on Arduino microcontroller - Mat Deris, Mohd Akram (2013)
Smartphone has become a very influential and vital device as it can do almost everything. Most of us would probably hate to carry a lot of things in their pocket when leaving the house. In this project, a door locking and turning off home appliances system using Android smartphone connected via Bluetooth connection protocol developed based on Arduino microcontroller was developed. The developed keyless system is hoped to assist user to lock and unlock the door without using keys and able to switch off or on the home electrical appliances by exploiting their smartphone. This system use an Android application which is specially designed to be connected via Bluetooth to the main system located in the house. Thus, the system developed is expected to help reduce the electricity bills and ease the user by just bringing their smartphone rather than having to carry a bunch of keys when leaving their house. User will find it much more convenience to lock the door just using smartphone rather than bringing keys.